Thyroid Papillary Microcarcinoma - Carcinoma with Clinically Benign Behaviour - Hitesh R Singhavi; Manish Mair; Burhanuddin Qayyumi; Arjun Singh; Pankaj Chaturvedi (Journal of Head & Neck Physicians and Surgeons)
Introduction: The availability of sensitive diagnostic procedures has led to an increased incidence of micropapillary thyroid carcinoma (mPTC) globally. Moreover, there has been a paradigm shift in the treatment of these cancers from total thyroidectomy to lobectomy to active surveillance. Methodology: To identify manuscripts with latent mPTCs, the database was searched and relevant articles were included in the manuscript. We have looked at the probable incidence of mPTC based on the autopsy report and World Bank population. Furthermore, the clinical behavior of mPTC is elaborated with its psychological and financial impact on the patients. Results: Based on the published autopsy reports, we estimated that around 8.7 million people would suffer from thyroid papillary microcarcinoma in 2018. This hypothetical number will easily outnumber the required number of thyroid surgeons to operate these cases. This will cause significant psychological distress to the patient by the word “cancer.” In addition, the incidence of bankruptcy is also higher in these patients as they live longer. Conclusion: We postulate that labeling thyroid papillary microcarcinoma as “Carcinoma with clinically benign behavior” might reduce the associated psychological distress as well as financial burden.